Caregivers' adherence to carbamazepine treatmentfor children and adolescents suffering from mentalhealth disorders - Hebe Karina de Oliveira Stucchi, Marli Gerenutti (Journal of Applied Pharmaceutical Science)
Carbamazepine is a well considered drug as mood stabilizer, having antipsychotics and antiepileptic effects. It has been mainly used in treating hyperactivity, aggression, dysphoric mood and pattern of rapid cycling. The purpose of this study is to evaluate adherenceto the carbamazepine treatment in children/adolescent suffering from mood disorders and the role of caregivers in the treatment solvability. Children/adolescent, outpatients, from CAPSi -Sorocaba/SP and their caregivers were invited to take part in this study. Data collection was carried out in three phases: identifying patients through the analysis of medical records and theusage of WHO ICD-10; applying a structured interview mentioning the patients' sociodemographic conditions; blood collection for carbamazepine serum measurement using FPIA technique. The children/adolescent present emotional and behavioral disorders, usually startingin the childhood or adolescence; it was observed, by the data collected in the interviews, that most caregivers understands the treatment; results of the serum measurement however, showed that 46.6% of the children presented serum measurement outside the therapeutic range. The results show that there are difficulties relating to the caregivers regarding compliance to the treatment with carbamazepine in children suffering from mood disorder, requiring the need of an intervention process in order to guarantee treatment.
Keywords: Carbamazepine,Caregivers adherence,Children,Mood disorders.